The interpretive mechanisms in the interpretation of Al-Basair by Sheikh Ya’soub Al-Din Al-Juwaibari (Journal of Misan Researches, 2024)
Interpretation is an important mechanism of discourse analysis, as it works to build meaning by recalling its internal structures of words, grammatical structure, morphological and rhetorical structures, and its external structures of reasons for revelation, textual parallels, doctrine, scientific references, etc.                                             The research focused on studying the most important major interpretive mechanisms (language, grammar) and minor (textual parallels, reasons for revelation) in the interpretation of Al-Basair; therefore, the study was divided into an introduction and two chapters.                                                                                                           The introduction dealt with defining the interpreter, interpretation and its methodThe first chapter: The minor internal interpretive mechanisms (language and grammar) The second section: The major external interpretive mechanisms (reasons for revelation, parallel texts, then we concluded our study with the most important results that the researcher reached, with a presentation of a list of sources and references.    It is worth noting that the reason for the researcher’s reliance on some minor and major textual mechanisms that interpretive analysis depends on to know the interpreter’s ability to use them is because they are considered among the most important means that the interpreter employs to understand the intention of God Almighty in his holly Quran and as a result of the enormity of the interpretation, it was impossible to address other mechanisms.